Study on the dynamic mechanical, flexural strength and some characteristics of polyoxymethylene/silica nanocomposites - Mai, Tran Thi; Trang, Nguyen Thi Thu; Chinh, Nguyen Thuy; Trung, Tran Huu; Hoang, Thai (Vietnam Journal of Science and Technology, 2021)
This work focuses on the reinforcement of polyoxymethylene (POM) by nanosilica particles (NS) in order to increase flexural strength and hardness of the POM matrix. Thermo - mechanical properties of the POM/NS nanocomposite were investigated by using dynamic mechanical thermal analysis (DMTA)